Body Mass Index and Waist Circumference of HIV-Infected Youth in a Miami Cohort: Comparison to Local and National Cohorts - Arbeitman, Lori E. (J Pediatr Gastroenterol Nutr, 2014)
OBJECTIVE: Human immunodeficiency virus (HIV) infected youth are healthier due to effective antiretroviral therapies (ARVs). We compared anthropometric measurements and prevalence of overweight and obesity between perinatally-HIV-infected youth, a local HIV-uninfected comparison group and 2007–2010 National Health and Nutrition Examination Survey (NHANES) data. In addition, we compared only African American HIV-infected to NHANES African American. METHODS: Height, weight, body mass index (BMI) and waist circumference (WC) of HIV-infected youth, age 10–19 years, were compared among groups. BMI percentiles were categorized as underweight (≤5%), normal (5–<85%), overweight (85–<95%), and obese (≥95%). Clinical correlates were modeled as predictors of BMI and WC. RESULTS: 134 HIV-infected (including 103 African Americans) (mean age 16.5y), 75 HIV-uninfected (mean age 14.2y), and 3216 NHANES (including 771 NHANES African Americans) (mean age 15.0y) youth were included in the analysis. Height and weight z-scores of HIV-infected were lower than HIV-uninfected and NHANES (P≤0.056). BMI, WC, and BMI category were not statistically different between groups. In the HIV-infected African American group, BMI z-score was lower (0.49 vs 0.76; P=0.04) compared to NHANES African American. There were no significant predictors of BMI or WC for the HIV-infected group. CONCLUSION: HIV-infected children have similar BMIs and WCs as uninfected children both locally and nationally and show similar high rates of obesity and overweight. However, when compared to a more racially similar African American national sample, HIV-infected children have a lower BMI, suggesting that there may be persistent anthropometric differences in HIV.